CO2 enrichment in greenhouse production: Towards a sustainable approach - Wang, Anran; Lv, Jianrong; Wang, Jiao; Shi, Kai (Frontiers in Plant Science, 2022)
As the unique source of carbon in the atmosphere, carbon dioxide (CO2) exerts a strong impact on crop yield and quality. However, CO2 deficiency in greenhouses during the daytime often limits crop productivity. Crucially, climate warming, caused by increased atmospheric CO2, urges global efforts to implement carbon reduction and neutrality, which also bring challenges to current CO2 enrichment systems applied in greenhouses. Thus, there is a timely need to develop cost-effective and environmentally friendly CO2 enrichment technologies as a sustainable approach to promoting agricultural production and alleviating environmental burdens simultaneously. Here we review several common technologies of CO2 enrichment in greenhouse production, and their characteristics and limitations. Some control strategies of CO2 enrichment in distribution, period, and concentration are also discussed. We further introduce promising directions for future CO2 enrichment including 1) agro-industrial symbiosis system (AIS); 2) interdisciplinary application of carbon capture and utilization (CCU); and 3) optimization of CO2 assimilation in C3 crops via biotechnologies. This review aims to provide perspectives on efficient COBody text (only plain text2 utilization in greenhouse production.